Active travel to non-school destinations but not to school is associated with higher physical activity levels in an ethnically diverse sample of inner-city schoolchildren - Lee Smith; Daniel Aggio; Mark Hamer (BMC, 2017)
Abstract Background This study investigated the association of travel mode to school and non-school destinations with objectively assessed health markers and physical activity in an ethnically diverse sample of inner-city UK schoolchildren. Methods We used data from the Camden Active Spaces project (n = 450 children aged 9.1 yrs) to examine associations of school travel mode and frequency of active travel to non-school destinations with daily and out-of-school physical activity, sedentary time and health markers; whilst controlling for appropriate covariates including objectively measured route length. Results High frequency of active travel to non-school destinations was associated with more time in moderate-to-vigorous physical activity during out-of-school periods (3.8, 0.8-6.9 min/d) and greater out-of-school (738, 197.4-1278.6 steps/d) and daily step counts (588.1, 51.6-1124.6 steps/d). No associations were observed between school travel mode, health outcomes and activity levels. Conclusion High frequency of active travel to non-school destinations is associated with higher levels of physical activity. These findings highlight the contribution of travel to non-school destinations to overall physical activity levels in schoolchildren.